(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
This article examines the crucial role of collaborative interventions by social workers and nurses in healthcare settings and the importance of evaluating their effectiveness. Social workers and nurses play complementary roles in addressing the multifaceted needs of patients, including psychosocial support, care coordination, and discharge planning. Evaluating these collaborative interventions is essential for optimizing patient outcomes, enhancing healthcare quality, and informing evidence-based practice. This paper discusses key metrics and methodologies for evaluating collaborative interventions, presents case studies of successful evaluations, and explores challenges and future directions. By highlighting the significance of evaluation in enhancing inter-professional collaboration, this article underscores the imperative for ongoing research and quality improvement efforts in healthcare delivery.